THE EFFECTIVENESS OF FUN EASY LEARN MEDIA TO IMPROVE VOCABULARY IN MARAH KALAM AT MTSN BATU - Mokoginta, Siti Mustika Vevi; Muassomah, Muassomah (UIN Maulana Malik Ibrahim Malang, 2022)
This research was conducted to obtain the results of the effectiveness of the fun easy learn media in learning maharah kalam. This study uses a quantitative method with the type of pre-experimental one design group. The data collection technique used by the researcher in this study was the initial test and the final test. Respondents amounted to 30 people who are students of class VII. Then in this analysis there are also differences before and after treatment in the use of fun easy learn to improve vocabulary mastery (mufrodat) in maharah kalam. Where the descriptive analysis got the average results of the pretest 33.33 and the posttest 71.97, the Normality Test got normal results with a pretest value of sig. 200 and posttest sig.0,015 and Paired Test sample T-Test get the results of the mean pretest 37.23 and posttest 81.43.